السياق ودوره في التفريق بين الحقيقة والمجاز: The Role of Context in Distinguishing between "Al-Haqiqa" and "Al-Magaz" - Ahmad Eldesoky, Ebrahim Mohammad; Zabidin, Mohd Azizul Rahman (SIBAWAYH Arabic Language and Education, 2024)
يتناول هذا البحث موضوع السياق ودوره في التفريق بين الحقيقة والمجاز، وتكمن مشكلة البحث في الوقوف على الفرق بين الحقيقة والمجاز في اللغة وبيان المفهوم الحقيقي لكل منهما وتوضيح هذا بالشواهد التطبيقية، وهل اللغة كلها مجاز أو كلها حقيقة أو أنها مزيج من هذا وذاك وكيف يكون عمل السياق في بيان الفرق بين الحقيقة والمجاز. ويهدف هذا البحث إلى بيان المفهوم الصحيح للحقيقة والمجاز والوقوف على الرأي الصحيح في قول ذهب إليه بعض علماء العربية مفاده: أن اللغة حقيقة كلها وأنكر المجاز وزعم أنه غير وارد في القرآن ولا في الكلام، وزعم بعضهم أن اللغة كلها مجاز وأن الحقيقة في اللغة لا وجود لها. ويهدف كذلك إلى بيان أن للسياق بنوعيه الحالي واللغوي دوراً في التفريق بين الحقيقة والمجاز. وقد اتبع البحث المنهج الوصفي التحليلي، فقام ببيان مفهوم المجاز والحقيقة ووصف كل منهما وصفا لغويا دقيقا يبين طبيعة كل منهما، أما من حيث التحليل والتطبيق فإنه يركز على الإشارة إلى النماذج اللغوية المتعددة من لغتنا العربية التي توضح توضيحا دقيقا الفرق بين الحقيقة والمجاز ومكان كل منهما وتوضيح كيف يكون للسياق بنوعيه اللغوي دور في التفريق بين الحقيقة والمجاز. هذا، وقد جاء البحث في ثلاثة مباحث تعقبها خاتمة مشتملة على نتائج البحث ثم تعقبها المصادر والمراجع. أما المباحث فجاءت على النحو التالي : المبحث الأول: مفهوم الحقيقة والمجاز وعلامات كل منهما . المبحث الثاني: سياق الموقف ودوره في التفريق بين الحقيقة والمجاز. المبحث الثالث: السياق اللغوي ودوره في التفريق بين الحقيقة والمجاز. وقد توصل البحث إلى عدد من النتائج أهمها:1- أن من علامات الحقيقة تبادر الذهن إلى فهم المعنى والعراء عن الحقيقة.2-لابد للحكم على تركيب ما أنه مجاز من علاقة و قرينة لغوية أو حالية.3-للسياق بنوعيه اللغوي والحالي دور كبير في وضع الحد الفاصل بين الحقيقة والمجاز. This research explores the theme of context and its role in distinguishing between "Al-haqiqa" and "Al-magaz" The primary objective is to elucidate the accurate concepts of "Al-haqiqa" and "Al-magaz "and to ascertain the correct stance regarding the assertion made by some Arabic language scholars, claiming that language is entirely literal, rejecting metaphor as nonexistent in the Quran and speech. Conversely, others argue that language is entirely metaphorical, with no room for "Al-haqiqa." Additionally, this study aims to highlight the dual role of context, both current and linguistic, in differentiating between Al-haqiqa" and "Al-magaz". The research adopts a descriptive-analytical approach, meticulously defining the concepts "Al-haqiqa" and "Al-magaz" linguistically. Through analysis and application, the focus shifts to multiple linguistic examples within the Arabic language that precisely illustrate the distinction between "Al-haqiqa and Al-magaz", elucidating the role of both situational and linguistic context in this differentiation. The study is organized into three sections, followed by a conclusion presenting the research findings, and a bibliography. The study is structured into three sections: Section 1 explores the concept of "Al-haqiqa and Al-magaz," along with their respective indicators. Section 2 examines situational context and its role in distinguishing between "Al-haqiqa and Al-magaz". Section 3 focuses on linguistic context and its role in distinguishing between" Al-haqiqa and Al-magaz". The study concludes by presenting research findings and includes a bibliography. The research yields several key findings, including firstly, the mind naturally associates "Al-haqiqa" with understanding the meaning and clarity. Secondly, the evaluation of whether a statement is metaphorical necessitates consideration of linguistic or situational relationships and indicators. Thirdly, both situational and linguistic contexts play a significant role in establishing a clear boundary between "Al-haqiqa and Al-magaz". Keywords: "Al-haqiqa", "Al-magaz", Relationship, Indicator, Linguistic Context, Situational Context